Glyphosate and AMPA in Human Urine of HBM4EU Aligned Studies: Part A Children - Buekers, Jurgen; Remy, Sylvie; Bessems, Jos; Govarts, Eva; Rambaud, Loïc; Riou, Margaux; Tratnik, Janja Snoj; Stajnko, Anja; Katsonouri, Andromachi; Makris, Konstantinos C.; De Decker, Annelies; Morrens, Bert; et al. (My University, 2022)
Few data are available on the exposure of children to glyphosate (Gly) in Europe. Within HBM4EU, new HBM exposure data were collected from aligned studies at five sampling sites distributed over Europe (studies: SLO CRP (SI); ORGANIKO (CY); GerES V-sub (DE); 3XG (BE); ESTEBAN (FR)). Median Gly concentrations in urine were below or around the detection limit (0.1 µg/L). The 95th percentiles ranged between 0.18 and 1.03 µg Gly/L. The ratio of AMPA (aminomethylphosphonic acid; main metabolite of Gly) to Gly at molar basis was on average 2.2 and the ratio decreased with higher Gly concentrations, suggesting that other sources of AMPA, independent of metabolism of Gly to AMPA in the monitored participants, may concurrently operate. Using reverse dosimetry and HBM exposure data from five European countries (east, west and south Europe) combined with the proposed ADI (acceptable daily intake) of EFSA for Gly of 0.1 mg/kg bw/day (based on histopathological findings in the salivary gland of rats) indicated no human health risks for Gly in the studied populations at the moment. However, the absence of a group ADI for Gly+AMPA and ongoing discussions on e.g., endocrine disrupting effects cast some uncertainty in relation to the current single substance ADI for Gly. The carcinogenic effects of Gly are still debated in the scientific community. These outcomes would influence the risk conclusions presented here. Finally, regression analyses did not find clear associations between urinary exposure biomarkers and analyzed potential exposure determinants. More information from questionnaires targeting exposure-related behavior just before the sampling is needed.
Keywords: AMPA; children; exposure; glyphosate; HBM; HBM4EU